1998
DOI: 10.1046/j.1365-2796.1998.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed chylomicron remnant clearance in subjects with heterozygous familial hypercholesterolaemia

Abstract: Objectives. To study the role of the LDL receptor in the clearance of chylomicron remnants in humans. Design. Chylomicron remnant clearance was studied in five untreated subjects with heterozygous familial hypercholesterolaemia (FH) and nine normolipidaemic controls, by oral retinyl palmitate-fat loading tests. Fasting plasma triglycerides (TG), which are important determinators of chylomicron and remnant clearance, were not significantly different between FH (1.76 Ϯ 0.32 mmol L Ϫ1 , mean Ϯ SEM) and controls (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Studies involving postprandial lipoprotein remnants with REs as a marker in homozygous or heterozygous FH patients revealed either abnormalities 12,38 or a normal removal of chylomicron remnants. 13,31 We confirmed an earlier report by Castro Cabezas et al 12 that postprandial chylomicron remnants reflected by REs in the SfϽ1000 fraction were elevated in heterozygous FH patients compared with matched control subjects. In the fasting state and the early postprandial period (first 3 hours after a meal), smaller sized chylomicrons (considered to be atherogenic) are secreted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involving postprandial lipoprotein remnants with REs as a marker in homozygous or heterozygous FH patients revealed either abnormalities 12,38 or a normal removal of chylomicron remnants. 13,31 We confirmed an earlier report by Castro Cabezas et al 12 that postprandial chylomicron remnants reflected by REs in the SfϽ1000 fraction were elevated in heterozygous FH patients compared with matched control subjects. In the fasting state and the early postprandial period (first 3 hours after a meal), smaller sized chylomicrons (considered to be atherogenic) are secreted.…”
Section: Discussionmentioning
confidence: 99%
“…8 Animal studies have shown that a deficiency in the LDL receptor is associated with a delayed chylomicron remnant removal. 9 -11 Castro Cabezas et al 12 have demonstrated a small but significant postprandial increase in retinyl palmitate concentration in the chylomicron remnant fraction (Svedberg flotation unit [Sf]Ͻ1000) in heterozygous FH patients compared with normolipidemic control subjects. However, Rubinsztein et al 13 did not observe any accumulation of vitamin A-labeled chylomicrons, IDLsized remnants, or chylomicron remnants in homozygous FH patients.…”
mentioning
confidence: 99%
“…Since FCHL and the metabolic syndrome share so many clinical characteristics and metabolic disturbances [5,17,18], it has always been difficult to separate the two disorders. One of the striking differences may be the mode of inheritance and the effects of environmental factors on the expression of the two phenotypes.…”
Section: Fchl and The Metabolic Syndromementioning
confidence: 99%
“…FCHL (familial combined hyperlipidaemia) is the most frequent familial dyslipidaemia resulting in premature atherosclerosis [1][2][3][4][5]. Several reports have suggested that FCHL is a monogenic disorder with different modifying genes [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation